The Path Integral Approach for the Nuclear Collective Motion - Galetti, D.; Mizrahi, S. S.; Pimentel, B. M. (IOP Publishing, 1983)
A procedure is developed for treating a nuclear collective motion via the path integral formalism by defining a collective propagator in the phase space of the collective subspace. This collective subspace is projected out of the full many-body Hilbert space by an approach of the Generator Coordinate Method. Under the approximation of quadratic momentum dependence we write the propagator in the coordinate representation from which we derive the collective Schrödinger equation in terms of a canonical pair P̂ and Q̂. © 1983 IOP Publishing Ltd.